The Effect of Emotional Regulation for the Successful Treatment of Emotional Dependence in Young People - Lobanov, Serhii; Voshkolup, Hanna; Zhylin, Mykhailo; Medvedieva, Olena; Usyk, Dmytro (International Journal of Statistics in Medical Research, 2025)
Regulation of one’s own emotional state is of great importance for a person’s mental health. The issue under research is related to determining emotional regulation approaches for the success of the treatment of emotional dependence in young people. Methods. It was possible to achieve the set goal based on the use of methods of analysis, observation, the Spann-Fischer Codependency Scale, and the Student’s coefficient. The emotional regulation approaches developed by the authors included social recovery, analysis of someone else’s problem and behaviour, problem solving, and art therapy. Results.It was found that the therapy had a positive effect on the respondents, enabling them to primarily develop the self-confidence skills (96%). Also, to develop a lack of need for constant approval (92%), and consideration of their own interests (93%). It was found that the level of the respondents’ emotional dependence decreased to a low level (84%) from the beginning of the study. The respondents noted that art therapy (53%) and socialization (47%), which became the basis of the treatment approaches, had almost the same positive effect. Conclusions.The practical significance of the article is related to the possibility of using effective approaches to regulating emotional dependence in young people. The research prospects will be aimed at comparing the impact of the developed approaches to regulating emotional dependence in young people and middle-aged people.